Development of Missouri Mathematics Project Learning Worksheet to Improve Mathematical Communication and Critical Thinking Skill - Wulandari, Alfianti Puspita; Cholily, Yus Mochamad; Ummah, Siti Khoiruli (Jurnal Pendidikan MIPA, 2022)
This study aims to develop a valid, effective, and practical mathematics learning tool. This study aims to develop student worksheets based on mathematical communication and critical thinking on data presentation material. The type of research conducted by researchers is research and development (R&D). This worksheet development model uses 4-D, namely the model from Thiagajar, among others: Define (defining), Design (design), Develop (development), Disseminate (deployment). Based on the purpose of this study, the worksheet develop by the researcher was declared valid with a final score of 3.89 which was obtained from the validation sheet of all instruments given to the two validators, namely lecturers and teachers and showed that it was feasible to be tested on students. The worksheets developed by the researchers were stated to be very practical with a final score of 84,93%, meaning that the worksheets were easy to use and achieved the learning objectives that had been determined. The worksheet developed by the researchers showed a very effective category with an average final score of 5.86% and an average N-Gain score of 0.55 and the percentage of N-gain scores was 55.73% with a moderate improvement category, meaning that the worksheet had influence on students so as to bring results in achieving learning objectives.Keywords: students’ worksheet, Missouri mathematics project, mathematical communication, critical thinking. DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp57-66